Flooding the lake? International democracy promotion and the political economy of the 2014 presidential election in Afghanistan. Issue 6 (1st November 2016) - Goodhand, Jonathan; Suhrke, Astri; Bose, Srinjoy
Abstract: The introductory article to this volume positions the Afghan case within the broader literature on the political economy of war-to-peace transitions. The paper begins by critiquing the rise of democracy promotion, and then employs a political economy framework to understand the more focused research on democratisation and elections. The paper highlights some of the major features of the Afghan case that provided a backdrop for the 2014 election: a deeply divided society, a highly militarised and invasive international presence, and a history of flawed elections. This discussion helps contextualise the seemingly technical questions about constitutional design, electoral systems and the organisation and monitoring of elections. It is argued that the pursuit of elections and democratisation efforts more broadly, in a context of growing insecurity and political fragmentation, have had unintended and perverse effects. The concluding section sets out the main themes of the individual contributions that follow.